PENERAPAN LEAN SIX SIGMA UNTUK MENINGKATKAN KUALITAS VOLUTE CASING DALAM MENGURANGI PRODUK CACAT - Dewi Yuliana; Saryatmo, Mohammad Agung; Salomon, Lithrone Laricha (Jurnal Mitra Teknik Industri, 2023)
Good product quality or not depends on factors that influence it such as the quality of raw materials used, production processes, production tools, skilled human resources and can work effectively to produce a product in the company. The company under study was founded in 1992 in the Pulo Gadung area, East Jakarta. This company produces a product in the form of pump casting. This pump casting has several types of products, such as volute casing, impeller, bearing housing, and casing cover. Based on the results of observations and so on, the three biggest wastes are defects, overproduction and waiting. The research was conducted utilizing the lean six sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) stage to minimize waste and create continuous improvements. After analyzing and processing the data, it was noted that the three biggest wastes during the production process were defects of 26.35%, overproduction of 22.90%, and waiting of 12.60%. Regarding the sigma and DPMO values, the DPMO calculation results obtained are 14,972 with a value. sigma is at 3,671. After providing recommendations for improvements to the problem, the duration of non-value added activity in value stream mapping was successfully reduced from 671,700 seconds to 361,080 seconds which increased the PCE value from 25.32% to 38.67%, with improvements the DPMO value is 4289 units and the sigma value after repair is 4.128.